2021
DOI: 10.3390/app112411593
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Liquid Crystalline Molecules on PDMS Surfaces and within PDMS Microfluidic Systems

Abstract: The unique components of PDMS-based microfluidic systems are those combined with liquid crystalline materials. Their functionality, especially when it comes to optical applications, highly depends on the LC molecular arrangement. This work summarizes experimental investigations on the orientation of molecules within LC:PDMS structures according to the manufacturing technologies. The availability of high-quality molds to pattern PDMS is a significant barrier to the creation of advanced microfluidic systems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Designs of any shape, including complex patterns with a resolution down to single micrometers, may be easily achieved. Moreover, the spontaneous vertical alignment (VA) 33 of LC molecules on the PDMS surface simplifies the fabrication procedures, making additional orienting layers needless. The primary concern when fabricating electrically driven structures, especially with sophisticated geometry, is creating a suitable and efficient electrodes' system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Designs of any shape, including complex patterns with a resolution down to single micrometers, may be easily achieved. Moreover, the spontaneous vertical alignment (VA) 33 of LC molecules on the PDMS surface simplifies the fabrication procedures, making additional orienting layers needless. The primary concern when fabricating electrically driven structures, especially with sophisticated geometry, is creating a suitable and efficient electrodes' system.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant alignment of NLC molecules within PDMS-embedded microchannels strongly depends on the channels' aspect ratio 58 , the quality of the molds used in the fabrication process 33 , and the method of connecting the PDMS chip to a substrate 59 . Based on previous studies 32 , 33 , 60 , 61 , it has been concluded that the best results in terms of predictability, reproducibility, robustness, and stability of LC molecular alignment in LC:PDMS structures are obtained for the molds obtained in the photolithography process 33 and with the assistance of the plasma treatment, reducing the PDMS surface roughness 60 , 61 . In fact, such procedures have been applied when fabricating the samples shown in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations